Facies analysis and depositional context of the Curitiba Sedimentar Basin geosite: new type section to Guabirotuba Formation - Vieira, Kimberlym Tábata Pesch; Fernandes, Luiz Alberto (Geologia USP. Série Científica, 2020)
The Curitiba sedimentary Basin geosite is an outcrop of the Guabirotuba Formation, a unit that fills the Curitiba Basin, in an urbanized area. The site, located on the capital of Paraná’s industrial region, gained notoriety due to the fossiliferous occurrences of Guabirotuba Fauna, one of the few fossil occurrences representing the Paleogene in the country and that defines a relative age for the fill of the basin. The facies analysis of the outcrop aimed to refine the knowledge about the unit’s sedimentary deposits and thus to contribute to future taphonomic and paleoenvironmental studies. For this purpose, methods of faciological analysis were used in three representative segments of the outcrop, in which sedimentary facies, architectural elements, eodiagenetic features (calcrete), and bedrocks. The compositional characterization of the sediments was complemented with petrographic analyses. The depositional context of the Guabirotuba Formation was interpreted as shallow channel deposits and floodplains of braided rivers in distributary fluvial systems. The facies of sands and gravels, in bars that fill channel features, were interpreted as proximal portions, where deposits of channels amalgamated by frequent avulsion. These deposits are interspersed with associations of mud, sheets, and sandy lenses, characterized as lateral spreading deposits in distal portions of the system. In the cuts that make up the outcrop, important fossiliferous discoveries have been made in recent years. This was one of the reasons that made the conservation area, protected by municipal decree. Considering such novelties, and the fact that the original Guabirotuba Formation section was hidden by urbanization, it is proposed to designate the outcrop as a type area and the set of sections as a new type-section of